How to make loop and sum the result ??

5 views (last 30 days)
ali
ali on 4 Jun 2014
Commented: Mahdi on 4 Jun 2014
I have this loop...
for i=1:3
A=x((i-1)*3+1);
B=x((i-1)*3+2);
C=x((i-1)*3+3);
R=A^2+B^3+A*c;
end
i have constriants D=7 or <7
so i need this costraint=D-C-M
let say M=2
my equestion is how can i have the sumuation result of C from loop three times and then add this sum to constraint equation???
Thank you.

Accepted Answer

Mahdi
Mahdi on 4 Jun 2014
for i=1:3
A(i)=x((i-1)*3+1);
B(i)=x((i-1)*3+2);
C(i)=x((i-1)*3+3);
R(i)=A^2+B^3+A*c;
end
Summation=sum(C);

More Answers (1)

ali
ali on 4 Jun 2014
Thank you Mahdi for answer, but i want the result value of c in each loop after sum add to eq .. constraint =D-C( sum of result in each loop)- M
  1 Comment
Mahdi
Mahdi on 4 Jun 2014
Just move the summation inside the for loop:
for i=1:3
A(i)=x((i-1)*3+1);
B(i)=x((i-1)*3+2);
C(i)=x((i-1)*3+3);
R(i)=A^2+B^3+A*c;
Summation(i)=sum(C);
end
In this case, each row of summation would correspond to the summation inside each iteration of the loop.

Sign in to comment.

Tags

No tags entered yet.

Community Treasure Hunt

Find the treasures in MATLAB Central and discover how the community can help you!

Start Hunting!

Translated by